IMPLEMENTASI PEMBELAJARAN BACA TULIS AL-QUR’AN DENGAN METODE TILAWATI PADA TPQ FASTABIQUL CHAIRAT TAKOMA TERNATE TENGAH - arfan, rahman fitrianto (Archipelago, 2023)
There are many methods of learning to read and write Al Qoran in Indonesia, among these learning methods is the Tiwalati method. This method is a method of learning to read and write the Qur'an using a classical learning method approach.The Tilawati method is considered more effective, because with the classical method students are more conducive and can follow the material together, so that there are no students who play while studying. In addition, every student who is tested by the teacher to read, will also be noticed by other students, so they know how to read.However, does this method work well in practice? This study reveals the implementation of the Tilawati method in one of the TPQs in Ternate City, it is TPQ Fastabiqul Chairaat Takoma.From the results of the study, it shows that learning to read and write the Qur'an with the Tilawati method at TPQ Fastabiqul Chairat generally goes well However, there are several obstacles, including; 1) participants in the class cannot be ascertained, because some schools in the city of Ternate take turns every week, they enter on an alternating schedule every week, so the santri’s cannot be grouped with certainty. 2) low discipline of students in participating in activities, this is due to low motivation, possibly due to lack of support from parents. 3) The biological factor is that female students who have entered their menstrual period cannot participate in recitation activities.                                                                           Keywords; Tilawati’s methode, Learning reading and writing Al Qoran